The madman of Piney Woods - Curtis, Christopher Paul (Scholastic Press, 2014)
Even though it is now 1901, the people of Buxton, Canada (originally a settlement of runaway slaves) and Chatham, Canada are still haunted by two events of half a century before--the American Civil War, and the Irish potato famine, and the lasting damage those events caused to the survivors.